2008
DOI: 10.1186/1471-230x-8-47
|View full text |Cite
|
Sign up to set email alerts
|

Bile composition in Alagille Syndrome and PFIC patients having Partial External Biliary Diversion

Abstract: Background: Partial External Biliary Diversion (PEBD) is a surgical intervention to treat children with Progressive Familial Intrahepatic Cholestasis (PFIC) and Alagille syndrome (AGS). PEBD can reduce disease progression, and examining the alterations in biliary lipid composition may be a prognostic factor for outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 37 publications
1
31
0
1
Order By: Relevance
“…Emerick et al demonstrated that ALGS patients at baseline had greater bile salt, cholesterol, phospholipid, and chenodeoxycholicto-cholic acid ratios than PFIC patients. (31) They also showed that following successful PEBD, ALGS patients have higher biliary lipid concentrations than PFIC patients, and that the FIC1 subtype of PFIC was associated with increased postoperative biliary phospholipic concentrations. Jericho et al studied the kinetics of bile acid turnover in 5 PFIC patients with successful PEBD compared to 5 PFIC patients who underwent LT (32) and observed comparable bile acid transport kinetics between the two groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Emerick et al demonstrated that ALGS patients at baseline had greater bile salt, cholesterol, phospholipid, and chenodeoxycholicto-cholic acid ratios than PFIC patients. (31) They also showed that following successful PEBD, ALGS patients have higher biliary lipid concentrations than PFIC patients, and that the FIC1 subtype of PFIC was associated with increased postoperative biliary phospholipic concentrations. Jericho et al studied the kinetics of bile acid turnover in 5 PFIC patients with successful PEBD compared to 5 PFIC patients who underwent LT (32) and observed comparable bile acid transport kinetics between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…The current study suggests that outcomes are much more complicated than one might glean from the existing published literature. Emerick et al demonstrated that ALGS patients at baseline had greater bile salt, cholesterol, phospholipid, and chenodeoxycholic‐to‐cholic acid ratios than PFIC patients . They also showed that following successful PEBD, ALGS patients have higher biliary lipid concentrations than PFIC patients, and that the FIC1 subtype of PFIC was associated with increased postoperative biliary phospholipic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The DKO mouse model develops cholestasis as early as 3 weeks of age and as such will be an excellent tool to study earlyonset cholestasis. Additionally, unlike that in diet-induced cholestasis (53), the DKO mice accumulate a range of both hydrophilic and hydrophobic BAs, similar to that in most clinical settings (54,55). Despite an early onset of liver damage, DKO mice remain viable for more than a year.…”
Section: Discussionmentioning
confidence: 99%
“…Although in some reports serum transaminase levels and pruritus improved in about half of the patients upon UDCA [102,104,105], in most studies UDCA was not effective [106][107][108][109][110][111][112][113]. Even in patients with a mild phenotype (BRIC1, BRIC2), UDCA did not prevent or abort a cholestatic attack [19,24,31,39,40,[114][115][116] (Table 2A).…”
Section: Udcamentioning
confidence: 81%
“…This innovative technique was quickly adopted by other centres worldwide and so far sixteen additional casereports/series addressing the effect and technique of PEBD in the treatment of PFIC have been published (Table 3). Except for one small series of five patients in which PEBD did not have any effect [104], all others report normalization or improvement of liver function in 75-100% of the patients with low GGT-PFIC, indicated by at least improved liver tests and reduced pruritus [106,108,110,112,[136][137][138][139][140][141][142][143]. The response in patients with an undefined subtype of PFIC seems to be less [111,144].…”
Section: Biliary Diversionmentioning
confidence: 97%